KNOWLEDGE AND PRACTICE ON JUNK FOOD CONSUMPTION AMONG HIGHER LEVEL STUDENTS AT SELECTED EDUCATIONAL INSTITUTIONS OF KATHMANDU, NEPAL - SUBEDI, SURAKSHA; NAYAJU, SUVASH; SUBEDI, SWETA; ACHARYA, ASTHA; PANDEY, ASHOK (International Journal of Research -GRANTHAALAYAH, 2021)
Background: Junk food is a term for food that is of little nutritional value and often high in fat, sugar, salt, and calories. Junk food can have a detrimental effect on levels of energy and mental well-being. Consumption of large quantities of junk food is associated with a drastic reduction in the consumption of nutritious foods such as milk, fruits and vegetables. High revenues, rapid urbanization, free home delivery, mouthwatering commercials and foreign cuisines have led to growing trend in the consumption of junk food. Purpose: The aim of this study was to assess the level of knowledge, prevalence, practice and influencing factors of junk food consumption among students of educational institutions of Kathmandu, Nepal. Methods: A Descriptive cross-sectional study was conducted. Total 367 participants were selected from educational institutions of Kathmandu using simple random sampling technique. Data were collected using Semi-structured Questionnaire by self-administered method. Findings: Around half (45.2%) of the respondent had poor level of knowledge, and only 19.1% of respondents had adequate knowledge regarding harmful effects of junk food consumption. All of the respondents had practice of junk food consumption. Research implications: The outcome of this study provides detailed understanding of not only knowledge, prevalence and practice of junk food consumption among students but also the reasons and influencing factors for students to consume junk food regardless of their knowledge on harmful effect and complications of junk food consumption. Practical Implications: The findings of this paper seeks to urge the concerned authorities to admit the fact that, the course with small topic regarding effects of junk food consumption alone cannot minimize the practice of junk food consumption among students, banning the advertisement which encourage the students to consume junk food is very crucial and to conduct the awareness programme regarding harmful effect of junk food consumption among all level of students through media and course work is necessary to prevent malnourishment and complications of junk food among students. Originality: This is the first survey regarding knowledge and practice on junk food consumption among students of educational institutions, and the area (educational institutions) were selected to collect the data from the students of various background (age, education level, ethnicity etc.) at same time, so that the results can be generalized among student.